KADAR AIR, KERAPATAN, DAN KADAR ABU WOOD PELLET SERBUK GERGAJI KAYU GALAM (Melaleuca cajuputi Roxb) DAN KAYU AKASIA (Acacia mangium Wild) - Fatriani Fatriani; Sunardi Sunardi; Arfianti Arfianti (EnviroScienteae, 2018)
The amount of fossil fuels is getting less and less daily, so to meet the human needs it needs to find alternative renewable energy sources, one of which comes from a plant (wood) known as wood pellet. The purpose of this study was to analyze the water content, density, and ash wood pellet ash powder of sawn galam and acacia. The moisture content produced by wood pellet meets Indonesian wood pellet standart (SNI 80212014), Germany (DIN 51371) and Austria (ONORM M 7135) The resulting density meets the German standard (DIN 51371) and Austria (ONORM M 7135). which fulfill the standard wood pellet from Indonesia (SNI 8021: 2014) and Germany (DIN 51371).